The truth about money - Edelman, Ric. (New York : Rodale, 2005)
A guide to money management and financial planning provides basic guidance on such topics as investments, long-term care, buying and selling real estate, retirement planning, getting out of debt, and affording college.
Includes bibliographical references and index.
Keywords: Finance, Personal